Analisis Karakteristik UKM Jaket Kulit di Kabupaten Garut dengan Menggunakan Model ”Diamond” Porter - Mulyati, Heti (IPB University, 2010)
The leather jacket industry is one of the strategic industry for local economy in Sub Province Garut, West Java. The aim of research is to analyzed characteristics of leather industry using The Diamond Porter (1990) model. The data were collected using questionnaire, survey, in depth interview and combination of them. The analysis was done by descriptive analysis. The study was conducted to leather industry in the area of Garut Kota and Karangpawitan suburb. It was found out that the continuity of the industry was supported by local conditions as well as municipal government. The research also revealed that the linkage among supporting industries such as raw material suppliers were very strong. Their linkage with local government was moderate, while the linkage with related industries such as banking, R & D institution or university was categorized as weak.